Futura study: evaluation of efficacy and safety of rupatadine fumarate in the treatment of persistent allergic rhinitis - Mion,Olavo de Godoy (2009)
Allergic rhinitis affects 10-30% of the population, negatively impacting one's quality of life and productivity. It has been associated with sinusitis, otitis media, sleep disorders, and asthma. Rupatadine is a second generation antihistamine with increased affinity to histamine receptor H1; it is also a potent PAF (platelet-activating factor) antagonist. It starts acting quite quickly, offers long lasting effect, and reduces the chronic effects of rhinitis. AIM: this study aims to assess the efficacy and safety of rupatadine in the treatment of persistent allergic rhinitis. MATERIALS AND METHOD: this is a multi-centric open prospective study. This study included 241 patients from 13 centers in Brazil and was held between October of 2004 and August of 2005. Signs and symptoms of rhinitis and tolerance to medication were analyzed after one and two weeks of treatment. RESULTS: reduction on general scores from 8.65 to 3.21 on week 2 (p<0.001). All signs and symptoms improved significantly in the first day of treatment (p<0.001), except for nasal congestion and secretion, which improved from the second day of treatment (p<0.001). Adverse events occurred in 19.9% of the cases, 27.7% on week 1. CONCLUSION: rupatadine effectively controls persistent allergic rhinitis; it is safe and presents low incidence of side effects.